Listeria-based vaccination against the pericyte antigen RGS5 elicits anti-vascular effects and colon cancer protection - Trevor S. Anderson; Amanda L. McCormick; Elizabeth A. Daugherity; Mariam Oladejo; Izuchukwu F. Okpalanwaka; Savanna L. Smith; Duke Appiah; Laurence M. Wood; Devin B. Lowe (OncoImmunology, 2023)
Colorectal cancer (CRC) remains a leading cause of cancer-related mortality despite efforts to improve standard interventions. As CRC patients can benefit from immunotherapeutic strategies that incite effector T cell action, cancer vaccines represent a safe and promising therapeutic approach to elicit protective and durable immune responses against components of the tumor microenvironment (TME). In this study, we investigate the pre-clinical potential of a Listeria monocytogenes (Lm)-based vaccine targeting the CRC-associated vasculature. CRC survival and progression are reliant on functioning blood vessels to effectively mediate various metabolic processes and oxygenate underlying tissues. We, therefore, advance the strategy of initiating immunity in syngeneic mouse models against the endogenous pericyte antigen RGS5, which is a critical mediator of pathological vascularization. Overall, Lm-based vaccination safely induced potent anti-tumor effects that consisted of recruiting functional Type-1-associated T cells into the TME and reducing tumor blood vessel content. This study underscores the promising clinical potential of targeting RGS5 against vascularized tumors like CRC.